الدور التنموي للتعايش في اشاعة روح التسامح - محمد ليلى حسن; حميد مرتضى محمد; بردي احمد وحيد (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
the modern concepts that were not known in our Islamic culture verbally, but its content is old, as sustainable development is a necessary need, life is not straight without it, but rather it is the basis of societies in general. Among research development is the process of establishing political institutions, their commitment to the democratic approach, and their availability of citizen participation in decision-making. The research showed that development is a continuous comprehensive or partial development process that takes different forms of well-being, stability and development in accordance with its social, intellectual and economic needs and capabilities.